Nessana necropoleis: An aerial and ground survey of Byzantine era cemeteries in the israeli Negev - Betzer, Pablo (Antiguo Oriente, 2021)
Nessana Necropoleis: An Aerial and Ground Survey of Byzantine Era Cemeteries in the Israeli Negev Using modern GIS and photogrammetry technologies, combined with traditional ground surveys, four ancients, previously unknown, cemeteries were found around the ancient site of Nessana, in the Negev desert. Comprising a total of 1,022 graves, these burial grounds were dated to the Byzantine period, although later burials, probably dated to the early twentieth century, were discern in two of them.